2012
DOI: 10.1007/s00229-012-0565-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Hölder regularity implying finiteness of integral Menger curvature

Abstract: Abstract. We study two kinds of integral Menger-type curvatures. We find a threshold value of α 0 , a Hölder exponent, such that for all α > α 0 embedded C 1,α manifolds have finite curvature. We also give an example of a C 1,α 0 injective curve and higher dimensional embedded manifolds with unbounded curvature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…The regularizing behaviour of this energy extends to general measurable sets X ⊂ R n (instead of a curve γ), see Scholtes [2012] and references therein. For higher-dimensional objects one first has to find an appropriate notion for R. We refer to [Lerman & Whitehouse, 2011] (for M 2 ), [Strzelecki & von der Mosel, 2005 and [Blatt & Kolasiński, 2011;Kolasiński, 2012a,b;Kolasiński et al, 2012;Kolasiński & Szumańska, 2011].…”
Section: Integral Menger Curvaturementioning
confidence: 99%
“…The regularizing behaviour of this energy extends to general measurable sets X ⊂ R n (instead of a curve γ), see Scholtes [2012] and references therein. For higher-dimensional objects one first has to find an appropriate notion for R. We refer to [Lerman & Whitehouse, 2011] (for M 2 ), [Strzelecki & von der Mosel, 2005 and [Blatt & Kolasiński, 2011;Kolasiński, 2012a,b;Kolasiński et al, 2012;Kolasiński & Szumańska, 2011].…”
Section: Integral Menger Curvaturementioning
confidence: 99%
“…Knowing that Σ is a compact, closed, C 1,λ/κ -submanifold of R n , we prove that also the constant M θβ from the (θ β) condition can be replaced by an absolute constant. Then we obtain estimates on the oscillation of tangent planes of Σ solely in terms of E, m, l and p. This allows to prove that the size of a single patch of Σ representable as a graph of some function is controlled solely in terms of E, m, l and p. Next we bootstrap the exponent λ κ to the optimal one α = 1 − ml p (see [14] and [1] for the proof that this is indeed optimal). Theorem 3.…”
Section: Introductionmentioning
confidence: 99%
“…This work already lead to a few other results. In our joint work with Szumańska [14] we have constructed an example of a function f ∈ C 1,α 0 ([0, 1] m ), where α 0 = 1 − m(m+1) p , whose graph has infinite E m+2 p -energy and we proved that for any α 1 > α 0 the graphs of C 1,α 1 functions always have finite energy. Later this result was complemented by our joint work with Blatt [1], where we have shown that a C 1 -submanifold of R n has finite E l p -energy for some p > m(l − 1) and l ∈ {2, .…”
Section: Introductionmentioning
confidence: 99%
“…Menger curvature for higher-dimensional objects has been discussed in [19,21,22,4,20,34]. Further information on the context of the integral Menger curvature within the field of geometric knot theory and geometric curvature energies can be found in the recent surveys by Strzelecki and von der Mosel [38,37].…”
Section: Introductionmentioning
confidence: 99%